Progress and Challenges of Nonfinancial Defined Contribution Pension Schemes : Volume 1, - Holzmann, Robert; Palmer, Edward; Palacios, Robert J.; Sacchi, Stefano (World Bank Publications, 2020)
The individual account-based but unfunded approach to mandated public pension systems is a reform benchmark for all pension schemes, promising fair and financially sustainable benefits. Nonfinancial defined contribution (NDC) pension schemes originated in Italy and Sweden in the 1990s, were then adopted by Latvia, Norway, and Poland, envisaged but not implemented in various other countries, such as Egypt and Russia, and remain under discussion in many nations around the world, such as China and France. In its complete form, the approach also comprises budget-financed basic income provisions and mandated or voluntary funded provisions. Volume 1 of this book offers an assessment of countries that were early adopters before addressing key aspects of policy implementation and design review, including how best to combine basic income provisions with an NDC scheme, how to deal with heterogeneity in longevity, and how to adjust NDC scheme design and labor market policies to deliver on reform expectations. Volume 2 addresses a second set of issues, including the gender pension gap and what family policies can do about it within the NDC framework, labor market issues and administrative challenges of NDC schemes and how countries are coping, the role of communication in these pension schemes, the complexity of cross-border pension taxation, and much more. Progress and Challenges of Nonfinancial Defined Contribution Pension Schemes is the third in a series of books analyzing the progress, challenges, and adjustment options of this reform revolution for mandated public pension systems.'Pension reform is a major issue in many countries. The development of the nonfinancial defined contribution pension plan in the 90's was a major advance in pension design. By reporting actual country experiences and exploring properties of plan designs, this latest collection of essays is a valuable contribution, well worth reading.' Peter DiamondProfessor at Massachusetts Institute of Technology; 2010 winner of the Nobel Memorial Prize in Economic Sciences 'A highly stimulating publication for policy makers and researchers alike. It pushes the analytical frontier for policy challenges that all public pension schemes are confronted with but that the nonfinancial defined contribution approach promises to handle best.' Noriyuki TakayamaPresident, Research Institute for Policies on Pension and Aging, Tokyo, and professor emeritus, Hitotsubashi University, Tokyo 'In a changing world where pensions are more than ever linked to labor markets, communication tools, and flexibility considerations, this anthology provides a unique up-to-date analysis of nonfinancial defined contribution pension schemes. By mixing international experiences and theoretical studies, it demonstrates the high adaptability of such pension schemes to changing social challenges.' Pierre DevolderProfessor of Finance and Actuarial Sciences, Catholic University of Louvain, Belgium.